Editorial Vol.20(1-2) - Rai, Vishnu S; Gnawali, Laxman; Manara, Christina; Luitel, Binod; Pandey, Gopal Prasad; Adhikari, Balaram; Neupane, Madhu (Journal of NELTA, 2015)
Journal of NELTA, Vol 20 No. 1-2, December 2015, page 5-15